Direito ao reconhecimento das terras ocupadas por quilombolas em Manaus - Pontes, Aldrin Bentes (2016)
This research Dissertation aims to bring a reflection on the official recognition of the lands occupied by quilombo in the state of Amazonas, but specifically in Manaus, in the Community of the Barranco de São Benedito, located in the district Square January 14, south of the capital area. It should be an analysis of the historical process of those community members who are remnants of slaves, coming mostly from Maranhão. The research will examine the right to collective ownership of the quilombos land, as the art. 68 of the Constitutional Provisions of the Brazilian Constitution ensures that the remaining quilombos who are occupying their lands are recognized definitive ownership, and the state must issue their bonds. The project is based on official documentary sources and oral accounts of the remaining themselves. These reports, which occur in the form of casual conversations, are important, since the documents and literature articles bring the idea that people Quilombos are isolated from society.